The role and impact of community health workers in childhood obesity interventions: a systematic review and meta‐analysis. (29th August 2018) - Schroeder, K.; McCormick, R.; Perez, A.; Lipman, T. H.
Summary: Childhood obesity increases the risk for poor health during childhood, as well as for adult obesity and its associated comorbidities. Children from racial/ethnic minority groups or who live in poverty experience elevated rates of obesity. One potential method for reducing childhood obesity disparities is to involve community health workers (frontline public health workers who are trusted members of and/or have an unusually close understanding of the community served). The purpose of this systematic review and meta‐analysis was to explore the role and effectiveness of community health workers in childhood obesity interventions. Eleven studies met inclusion criteria, of which nine were eligible for inclusion in the meta‐analysis. Results demonstrated that community health workers played various roles in childhood obesity interventions in the home, clinic, school, and community setting. Interventions focused primarily on children from underserved populations. Meta‐analytic findings demonstrated a small but significant impact on BMIz and BMI percentile (BMIz [7 studies]: −0.08, 95% CI: −0.15, −0.01, p  = 0.03, I 2  = 39.4%; BMI percentile [2 studies]: −0.25, 95% CI: −0.38, −0.11, p  < 0.01, I 2  = 0%). Findings from this review demonstrate that partnering with community health workers may be an important strategy for reducing childhood obesity disparities and advancing health equity.